HOSTOVSKY'S LONGING FOR A LOST PARADISE: INVENTING THE PAST - Zetova, Marie (Bohemica Olomucensia, 2021)
The paper presents a comparative reading of 1930s novels by Egon Hostovsky Dum bez pana and Pripad profesora Kornera. The attention is focused on the poetics associated with the themes of memory and recollection, especially on the role protagonists' memory plays in the constitution of identity of the narrating subject and other characters. It is shown that memory of the protagonists is rather unreliable and unstable, and so is their identity, because it seems to stem precisely from memory itself. It is suggested that this understanding could bring some useful insights for further interpretation of Hostovsky's later texts written in exile, where memory and subjectivity of the protagonists seem to be even more disintegrated - to the point, where differentiating between separate characters and events becomes almost impossible for the reader.
Keywords: Egon Hostovsky; memory; recollection; narrative identity; Paul Ricoeur; fiction; nostalgia